A conformal FDTD software package modeling antennas and microstrip circuit components. - Yu, Wenhua (IEEE Antennas & propagation magazine.)
This paper describes a conformal finite-difference time-domain (CFDTD) software package, and presents its applications to RF antennas and microstrip circuit components. The program includes a Visual Basic GUI, for graphically inputting the object geometries, setting source and boundary conditions, generating a non-uniform mesh, and post-processing of the data. A robust CFDTD technique is employed to handle conductors with curved surfaces and edges. Illustrative examples that show the application of the code for modeling antennas as well as microstrip discontinuities are presented in the paper.